Battery energy storage performance in microgrids: A scientific mapping perspective. (November 2022) - Zarate-Perez, Eliseo; Rosales-Asensio, Enrique; González-Martínez, Alberto; de Simón-Martín, Miguel; Colmenar-Santos, Antonio
Abstract: Microgrids integrate various renewable resources, such as photovoltaic and wind energy, and battery energy storage systems. The latter is an important component of a modern energy system, as it allows the seamless integration of renewable energy sources in the grid. The research here presented aimed to develop an integrated review using a systematic and bibliometric approach to evaluate the performance and challenges in applying battery energy storage systems in microgrids. Search protocols based on a literature review were used; this included thematic visualization and performance analysis using the scientific mapping software SciMAT (Science Mapping Analysis Software Tool). The results show that optimization methods in battery energy storage systems are important for this research field. In research works, they are interested in applying methods to reduce costs; this includes considering the state of charge, the degradation rate, and battery life. Developing an optimal battery energy storage system must consider various factors including reliability, battery technology, power quality, frequency variations, and environmental conditions. Economic factors are the most common challenges for developing a battery energy storage system, as researchers have focused on cost–benefit analysis.